2018
DOI: 10.4103/jispcd.jispcd_447_17
|View full text |Cite
|
Sign up to set email alerts
|

Molar protraction using miniscrews (temporary anchorage device) with simultaneous correction of lateral crossbite: An orthodontic case report

Abstract: Early loss of permanent teeth, congenitally missing lateral incisors or second premolars, extremely displaced or impacted canines, all result in a reduced upper dentition. That leads to the development of crossbite in the maxillary dentition. Partial denture prosthesis, dental implants, and space closure by fixed orthodontics are the various means of treating the edentulous spaces. Protraction of molars is time taking and challenging. Temporary anchorage device (TAD) helps to protract molars without anchorage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…It has been shown in the literature that TADs are successful in protracting the dentition to close spaces for missing teeth [38,39]. In the present study, a higher percentage of the dental students selected "a prosthetic implant" compared to those who elected "molar protraction".…”
Section: Discussionmentioning
confidence: 48%
“…It has been shown in the literature that TADs are successful in protracting the dentition to close spaces for missing teeth [38,39]. In the present study, a higher percentage of the dental students selected "a prosthetic implant" compared to those who elected "molar protraction".…”
Section: Discussionmentioning
confidence: 48%
“…Some studies have shown that there is a need for high anchorage control in molar protraction; according to them, with insufficient anchorage, there is a possibility of tipping of the molar and root resorption [52]. In an earlier research [53], in general, placing the miniscrew in the buccal area (due to the passage of the force through the buccal side of the center of resistance) could lead to unwanted expansion, while placing the miniscrew in the palatal area will reduce the width of the arch [53].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the unwanted side effects of molar protraction were a buccal force, tipping of adjacent teeth, mesial rotation and buccalization of molar teeth, and crossbite [50]. In the study of Marusamy et al [52], during maxillary molar protraction, the archwire needs to be expanded at each visit to prevent crossbite due to tooth movement to a narrower arch area [52]. In the study of Holberg et al [30], mandibular molar protraction was compared using dental anchorage and miniscrew.…”
Section: Discussionmentioning
confidence: 99%
“…2 The treatment of choice in treating edentulous area should be the least invasive option that complies the expected esthetic and functional objectives. 3 In orthodontic treatment option, the protraction of second molars to the edentulous area becomes the preferred choice, with the support of bones and good oral hygiene. Orthodontic movement could be an excellent way to regain new alveolar bone and soft tissue when closing spaces and avoid crestal bone damage mesial to the second molars.…”
Section: Introductionmentioning
confidence: 99%